2021
DOI: 10.1039/d0sc04889e
|View full text |Cite
|
Sign up to set email alerts
|

A photo-sensitizable phage for multidrug-resistant Acinetobacter baumannii therapy and biofilm ablation

Abstract: APNB for multidrug-resistant A. Baumannii therapy and biofilms ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…Due to acid microenvironment of S. mutans biofilm, the Ce6 was protonated and released; then, SiO 2 -P Ce6-IL changed to positive charged SiO 2 -P IL + . The biofilm had anions such as carboxyl, phosphoryl, and glycerate at the proteins or polysaccharides would produce negatively charge [19]. The electrostatic interactions would occur between SiO 2 -P IL + and S. mutans biofilm.…”
Section: Resultsmentioning
confidence: 99%
“…Due to acid microenvironment of S. mutans biofilm, the Ce6 was protonated and released; then, SiO 2 -P Ce6-IL changed to positive charged SiO 2 -P IL + . The biofilm had anions such as carboxyl, phosphoryl, and glycerate at the proteins or polysaccharides would produce negatively charge [19]. The electrostatic interactions would occur between SiO 2 -P IL + and S. mutans biofilm.…”
Section: Resultsmentioning
confidence: 99%
“…While phage cocktail combined with levofloxacin and amikacin, did not act synergistically ( 325 ). An excellent method of inhibiting A. baumannii biofilm was devised by Ran et al ( 326 ) by combining photodynamic bacteriophages (ABP) and Nile blue photosensitizers (NB). NB photosensitizer possessing sulfur atom displayed ROS production ability.…”
Section: Strategies Of Preventing a Baumannii Biof...mentioning
confidence: 99%
“…NB photosensitizer possessing sulfur atom displayed ROS production ability. Both in vitro and in vivo experiments proved that NB-phage bioconjugate (APNB) could bind to the main components of biofilms and reduce drug resistance caused by biofilms ( 326 ).…”
Section: Strategies Of Preventing a Baumannii Biof...mentioning
confidence: 99%
“…Second, the phage displayed exogenous peptides or chemical modifications, which could combine with inorganic nanomaterials/drugs, to form phage-nanocomplexes and drugloaded phages. It is well utilized in photodynamic cancer therapy (62)(63)(64). Some researchers used the Fd phage to display a cancertargeting peptide on pVIII major coat protein, and then conjugated photosensitizer at the N-terminal end of the targeting peptides, and demonstrated that the complex of phage-photosensitizers was able to selectively target and kill SKBR3 tumor cells in vitro (65).…”
Section: Ff Phage a Targeted Therapy Vectormentioning
confidence: 99%